Obstructive sleep apnea in sarcoidosis and impact of CPAP treatment on fatigue - Mari, Pier-Valerio; Pasciuto, Giuliana; Siciliano, Matteo; Simonetti, Jacopo; Ballacci, Federico; Macagno, Francesco; Iovene, Bruno; Martone, Filippo; Corbo, Giuseppe Maria; Richeldi, Luca (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Rationale: An increased incidence of Obstructive Sleep Apnea (OSA) in sarcoidosis has been described in small sample size studies. Fatigue is common in sarcoidosis and OSA could be a relevant, treatable comorbidity. To date, the effect of Continuous Positive Airway Pressure (CPAP) on fatigue has never been assessed. Objectives: To investigate the prevalence of OSA in sarcoidosis, fatigue status and daytime sleepiness in patients of our center. To explore the effect of CPAP in fatigue and daytime sleepiness after 3 months using validated questionnaires. Method: Single group, one center, open-label prospective cohort study. Measurements and main result: We enrolled 68 patients and OSA was diagnosed in 60 (88.2%): 25 (36.8%) were mild while 35 (51.5%) were moderate-to-severe. 38 (55.9%) patients received CPAP but only 20 (30.9%) were compliant at 3-month evaluation. Questionnaires demonstrated fatigue in 34 (50%) and daytime sleepiness in 21 (30.9%). In multivariate regression analysis, Scadding stage and FAS behave as predictors of Apnea-Hypopnea Index (AHI) severity while sleepiness and steroids weren’t associated. FAS score (ΔFAS = 6.3; p = 0.001) and ESS score (ΔESS = 2.8; p = 0.005) improved after three months of CPAP. Conclusions: OSA is highly prevalent in patients affected by sarcoidosis. ESS questionnaire is not reliable for OSA screening and other pre-test probability tool should be evaluated in further studies. CPAP leads to a significative reduction of fatigue and daytime sleepiness at three-month. Further studies are needed to confirm the high prevalence of OSA in sarcoidosis and the positive role of CPAP in fatigue.